THE INFLUENCE OF RECRUITMENT AND JOB TRAINING ON EMPLOYEE PERFORMANCE - Tarmidi, Didi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the recruitment, job training and employee performance of CV. Megah Karya and as well to find out how big the influence of the recruitment and job training to the employee performance of CV. Megah Karya. Research method used is descriptive-verification method. The sample in this research are the production employees of CV. Megah Karya as much as 30 respondents. The technique used in sampling is nonprobability sampling with saturated sampling technique. The data processing is done by classical assumption test, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing (t and F test). Based on the research results can be concluded that there is no significant influence between the recruitment to the employee performance of CV. Megah Karya. There is significant influence between job training to the employee performance of CV. Megah Karya and there is significant influence between recruitment and job training simultaneously to the employee performance of CV. Megah Karya, while the rest is influenced by variable outside this research.